Video-assisted endogastric resection of Polypoid Injury - Rodríguez, Gustavo; Mauccione, Andrea; Plazzotta, Cecilia; Balboa, Oscar (Cirugía del Uruguay, 2003)
Endogastric surgery or endoluminal laparoscopic surgery is a branch of the minimum invasive surgery which combines flexible endoscopy with laparoscopy, trocars being applied directly into the gastric lumen.